159 Relationships among circulating prolactin concentrations, hair coat score, and weights of grazing cows. (29th July 2019) - Davis, Erin; Cauble, Reagan; Powell, Jeremy G; Lester, Toby D; Gragg, Walker; Kutz, Bryan; Rosenkrans, Charles
Abstract: Prolactin (PRL) is a pleiotropic protein hormone synthesized and released from the anterior pituitary. Concentrations of PRL can serve as a biomarker of cattle exposure to ergot alkaloids. Our objective was to determine relationships among prolactin concentrations, hair coat score, and body weights of non-lactating crossbred beef cows (n = 71). Cows were weighed, hair coat scored (1 = 100% shed, and 5 = 0% shed), and blood samples collected in May, June, and July. Cows were grazing mixed grass pastures that included native endophyte-infected tall fescue. Serum PRL concentrations were determined by validated RIA. Based on May samples, cows were categorized as high (n = 11; 159 ± 29 ng/mL PRL), medium (n = 48; 51 ± 4 ng/mL PRL), or low (n = 12; 21 ± 4 ng/ mL PRL). Data were analyzed with Pearson correlations, and repeated measures ANOVA with month and prolactin category (PRLCAT) as main effects. Concentrations of PRL were correlated (r > 0.53; P < 0.0001) over the three months, and May PRL concentrations were correlated (r > 0.29; P < 0.02) with cow body weights in May, June, and July. Cows in the low PRLCAT had lower (P < 0.01) concentrations of PRL in all three months. Hair coat score decreased (P < 0.0001) each month (4.3, 2.7, and 1.3; respectively, May, June, July), and was higher (P < 0.05) for cows with low PRLCAT (3.3 vs. 2.7 and 2.4 for low, medium, and high, respectively). Cow body weight increased (P < 0.0001) from May to July. Cows in the low PRLCAT had lower (P < 0.05) body weights than medium and high PRLCAT cows (484 vs. 555, and 575 kg; respectively). Concentrations of PRL in May could be useful in identifying cattle with slick hair coats and heavier body weights.